Validity and reliability of the 7Cs positive youth development model instrument for physical education - Aang Rohyana; Amung Ma’mun; Tite Juliantine; Dian Budiana; Cucu Hidayat; Agus Arief Rahmat; Lalu Hulfian (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The 7Cs scale remains very limited in Indonesia and in physical education learning among senior high school students.